Access to Medicines for Non-Communicable Diseases (NCDS) during COVID-19 in Kenya: A Descriptive Commentary - Zana Wangari Kiragu; Gladwell Gathecha; Martin K. Mwangi; Zachary Ndegwa; Sonak Pastakia; Daniel Nyagah; Richard N. Cizungu; Mariana Takah Mutwiri; Meshack Ndolo; Veronika J. Wirtz (Taylor & Francis Group, 2021)
Evidence shows that those with non-communicable diseases (NCDs) are at higher risk for serious illness and mortality from COVID-19. In Kenya, about 50% of the COVID-19 patients who have died had an NCD. We sought to describe the challenges faced in accessing NCD medicines in Kenya during the pandemic, through a descriptive narrative informed by key stakeholders engaged in NCD service delivery and decision-making. Access to NCD medicines was affected at three levels, service delivery, health facility information systems and the medicines supply chain to health facilities. In response to these gaps, the Ministry of Health released clear directives and interim guidelines for continuity of NCD service delivery. However, implementation of guidelines was not apparent from conversations with county officials or from assessment of county services by the Ministry. Rather, heterogeneity was observed in counties' responsiveness to patient needs, where 5 out of 13 counties used mHealth technologies, while 5 had no established system to reach patients. COVID-19 amplified gaps that already existed in the system-particularly around lack of robust supply chains and sub-optimal health information systems. This descriptive paper will be useful to policy makers to provide a summary of the key challenges faced in accessing NCD medicines, identify gaps in medicines delivery, and make case for establishment of a more equitable health system to meet the needs of lower-income NCD patients.